Pengaruh Variasi Zeolit Clinoptilolite pada Pirolisis Limbah Plastik PP dan PE terhadap Karakteristik Minyak serta Nilai Kalor dan Viskositas - Ziddan Al Fachry; Mokh. Hairul Bahri; Nanang Saiful Rizal (Lembaga Pengembangan Kinerja Dosen, 2026)
The increasing generation of plastic waste has become a significant environmental concern due to its resistance to natural degradation and its potential to cause long-term pollution. Pyrolysis offers a promising approach for converting plastic waste into valuable liquid fuels while reducing environmental burdens. This study investigates the effect of clinoptilolite zeolite catalyst concentration on the characteristics of pyrolysis oil derived from mixed Polypropylene (PP) and Polyethylene (PE-HDPE) plastic waste. An experimental method was employed using catalyst concentrations of 0%, 5%, 10%, and 15% under a pyrolysis temperature of 550°C for 2 hours. The resulting liquid products were evaluated based on their calorific value and kinematic viscosity. The results demonstrated that catalyst addition significantly influenced fuel quality. The highest calorific value was obtained at a catalyst concentration of 5%, reaching 11,521.45 cal g⁻¹, indicating enhanced energy content compared to other treatments. Meanwhile, calorific values at catalyst concentrations of 0%, 10%, and 15% were 9,865.55 cal g⁻¹, 10,618.11 cal g⁻¹, and 9,377.89 cal g⁻¹, respectively. Increasing catalyst concentration also reduced the viscosity of the pyrolysis oil, from 1.215 mm² s⁻¹ at 0% catalyst to 0.652 mm² s⁻¹ at 15% catalyst, suggesting more effective cracking of long-chain hydrocarbons into lighter fractions. The viscosity value closest to the commercial gasoline standard was achieved at a catalyst concentration of 10% (0.790 mm² s⁻¹). Overall, clinoptilolite zeolite proved effective in improving the physicochemical properties of pyrolysis oil, with a 5% catalyst concentration providing the most favorable performance in terms of energy content. These findings highlight the potential of catalytic pyrolysis as a sustainable strategy for plastic waste valorization and alternative fuel production